Triple Feedback Hybrid (TFH) GIS Learning Framework: A Learning-Crime Solution Amalgamation - Lubrica, Nathaniel Vincent A. (JPAIR Multidisciplinary Research, 2013)
In the past decades, Geographic Information System (GIS) became a powerful tool in policing. However, a niche in the andragogy of GIS training was found. Thus, a Triple Feedback Hybrid (TFH) GIS Learning Framework was formulated to facilitate the learning process. A GIS utility model (GUM) was developed based on a real and specific problem scenario. Afterwards, the learning objectives of the training module syllabus were conveniently contrived as a simulation of the GUM procedure. In connection, module testing through trainings was conducted to equip police personnel with GIS application. It was found that participant attitude and leadership commitment played a central role in GIS learning and implementation. Moreover, focus groups with staggered phasing of trainings provided more attainable learning objectives, adequate time for mastery, and opportunity for reflective learning. As a result, the implementation of GIS in the Baguio City Police (BCPO) became a policy. Furthermore, the humble start of the research made an imprint as a best practice in rationalizing police operations, enhancing crime prevention, and engaging community policing in the regional and national level.